2006
DOI: 10.3171/ped.2006.105.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative ultrasonography used to determine the extent of surgery necessary during posterior fossa decompression in children with Chiari malformation Type I

Abstract: In patients who undergo decompressive surgery for CM-I, intraoperative ultrasonography may be a useful tool to aid the surgeon in deciding whether to opt for bone removal only or bone removal plus duraplasty and tonsillar shrinkage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
2
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 20 publications
3
66
2
8
Order By: Relevance
“…Recent studies have reported an incidence rate as high as 70% for syringomyelia [7,8,9,10] and hydromyelia [11,12,13], the two most common associated conditions. The mechanisms for the development of these conditions are still controversial and currently under investigation [1].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported an incidence rate as high as 70% for syringomyelia [7,8,9,10] and hydromyelia [11,12,13], the two most common associated conditions. The mechanisms for the development of these conditions are still controversial and currently under investigation [1].…”
Section: Discussionmentioning
confidence: 99%
“…These satisfactory neurological results in approximately three-quarters of all patients correspond with the similarly good improvement/resolution of syrinx. [154][155][156][157][158][159] However, only 16% of these series reported postoperative headache outcomes. As the other aspects of postoperative results showed, the improvement or resolution of headaches was also good, occurring in 73% of adult patients, 88% of pediatric patients, and 81% in all patients (Fig.…”
Section: Postoperative Outcomes: Neurological Statusmentioning
confidence: 99%
“…In a retrospective study, Yeh et al concluded that ultrasonography may be a useful tool to aid the surgeon in deciding which patients require duraplasty. 29 In that study, only 10% of patients in whom adequate CSF flow was seen on ultrasonography after bone decompression eventually required reoperation for persistence or recurrence of symptoms. On the other hand, a retrospective study by McGirt et al concluded that intraoperative ultrasonography may not effectively select patients in whom bone decompression alone is sufficient, as ultrasonography-guided decompression alone was associated with a 2-fold increased risk of symptom recurrence compared with patients who also underwent duraplasty (p = 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…5,9,24 As a result of these complications, many surgeons have moved toward less invasive surgical treatments such as "extradural decompression" alone, which involves bony decompression plus or minus thinning or splitting of the dura without actually entering the intradural space. 6,7,17,20,29 The theoretical advantages associated with this less invasive technique include reduced operative times, lower rates of CSF leakage and postoperative complications, and reduced postoperative hospital stay. 20 While there is growing evidence in the literature that many patients with CM-I can be effectively treated by posterior fossa decompression without duraplasty, there is no consensus regarding which surgical technique is the preferred treatment for CM-I.…”
Section: Discussionmentioning
confidence: 99%